OPTIMASI PENEMPATAN DISTRIBUTED GENERATION PADA PENYULANG GOA LAWAH MENGGUNAKAN METODE PARTICLE SWARM OPTIMIZATION (PSO) - Bagas Sastra Negara, I Made; Satriya Utama, Ngakan Putu; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i02.p10, 2018)
Distributed Generation (DG) is a small-scale power plant located close to the center of load. Goa Lawah feeder is a broadcast that is close to the potential of DG namely the Mini Hydro Power Plant on the Unda River in Klungkung Regency. In this research the optimization of Distributed Generation placement to Goa Lawah feeder. Optimization of Distributed Generation placement aims to reduce the value of loss of power that exist in the feeder Goa Lawah. The results of the research obtained at the point of bus 123 by Distributed Generation placement using Particle Swarm Optimization (PSO) method, with power loss 41 kW (44%). The initial loss before the Distributed Generation interconnection of 72 kW after the Distributed Generation interconnection to 31 kW.